Przedmiot metaforyczny - Mazur, Krzysztof (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2022)
The author focuses on a specific aspect of a metaphor is, i.e. on a metaphorical object, which in contemporary art often plays a key role. He focuses on the differences in depicting an object on a plane and in space, accentuating a particular complexity of the role of the metaphorical object in spatial arts. The paper discusses basic aspects, such as: • a ready object • a transformed object • an object as an inspiration and transposition into a sculpting form To better illustrate the topic, the author presents and briefly describes from the metaphorical point of view a few examples of works of spatial art by various artists using the same object.
Keywords: obiekt; metafora; przestrzeń; instalacja; rzeźba; object; metaphor; space; installation; sculpture